Nosocomial SARS‐CoV‐2 transmission in postoperative infection and mortality: analysis of 14 798 procedures. Issue 13 (8th October 2020) - Elliott, J. A.; Kenyon, R.; Kelliher, G.; Gillis, A. E.; Tierney, S.; Ridgway, P. F.
Abstract : This study used a national administrative database to estimate perioperative SARS‐CoV‐2 infection risk, and associated mortality, relative to nosocomial transmission rates. The impact of nosocomial transmission was greatest after major emergency surgery, whereas laparoscopic surgery may be protective owing to reduced duration of hospital stay. Procedure‐specific risk estimates are provided to facilitate surgical decision‐making and informed consent. Estimated risks